CONTRIBUTIONS OF OPERATIONS MANAGEMENT TO THE COMPETITIVENESS OF THE BRAZILIAN ELECTRONICS SECTOR - Lopes de Sousa Jabbour, Ana Beatriz [UNESP]; Chiappetta Jabbour, Charbel Jose [UNESP] (Vilnius Gediminas Tech Univ, 2013)
The objective of this paper is to identify and analyze various aspects of the internal and external operations management of Brazil's electronics sector and to consider the opportunities for and the threats to increasing the competitiveness of its participation in the global supply chain. To address this shortage in the literature, a survey of Brazilian Electric and Electronic Industry Association (ABINEE) companies was conducted. The collected data were complemented with secondary data to establish an overall view of the electronics sector in Brazil. The results suggest that electronics product assembly companies have the opportunity to invest more in information technology to expand process integration, plan and develop products, integrate customers, and maintain rather than expand their supply chain practices. The alignment between internal and external operations management becomes important in this context. The originality of this paper lies in its clarification of operations management in an economically important sector and the insight it provides to academics, practitioners and policy makers involved in the domestic and international electronics sector.
Keywords: Operations Management; Electronics sector; Supply Chain Management; Brazil